#TITLE_ALTERNATIVE# - SAMUEL NABABAN (NIM : 12807027); Pembimbing : Dr. Plato Martuani Siregar, M.Si, S.Si, OSWALDZ
Upstream part of Ciliwung watershed spread from Pangrango Mountain region to the KatulampaÃ‚Â’s weir that serves as to protect and buffer main watersheds that affect the potential flooding in Jakarta . Meteorological factors associated with the river discharge, water level and rainfall intensity. River discharge used to determine the occurrence of floods and flood mitigation process. For mitigation and discharge data processing, the data required as height of water that can be obtained at the actual time. Discharge measurements manually by the operator is particularly vulnerable to errors in reading the data so it can produce a fatal error when the data recorded is not the actual data . Therefore, we need a water level gauges that can take practical data and can transmit data at any time. Measurements carried out in the Katulampa weir area. Water level data is converted to discharge data using manning method. Rainfall data is converted to discharge data using HEC HMS models and overall data will be compared to obtained correlation and RMSE between data. Overflow water calculated by Muskingum method. Based on discharge results of the HEC HMS models with rainfall , land use and soil type as input data are compared with the calculated discharge with manning method using instrumentation tool and also weir station discharge data. Land use and soil type which is dominated with latosols influence the amount of water that entering the river caused by the rain. All flow data from devices processed by the manning method compared with data result on discharge data from weir station and have a good correlation result. In this study, a high correlation between the data of water equipment with water height data from weir station have 0.89 in the result, it states that the automatic water level measurements sensor is feasible sensor to use while calibration field done, because it has the same pattern in the movement of data, whereas the water level RMSE value of AWLR 25,9cm states that the sensor still need to calibrate to makes the best accuracy of the data so the sensor to be more fit for use as a counter height of water in the field by performing a calculation field as needed.